Root morphology analysis of posterior teeth using intraoral periapical radiograph - Fitri Yunita BATUBARA; Dewi KARTİKA (Journal of Syiah Kuala Dentistry Society, 2022)
Oral and dental health problems are still a part of ongoing national health issues in Indonesia.Through endodontic treatment, also called root canal treatment, a decayed tooth can still be preserved and restoredto its original form. It is done if the dental infection has spread into the pulp or the tooth has become nonvital due totrauma or accident. Root morphology is one of the main concerns before performing endodontic treatment. Aperiapical radiograph taken with bisecting and paralleling techniques is the first method in intraoral radiographicexamination to assist dental diagnosis and case management. This research aimed to analyze the mean length ofposterior teeth using an intraoral periapical radiograph and the difference in posterior teeth length in differentvertical angulations. A total of four extracted lower premolars and four extracted lower molars served as samples inthis analysis. They were mounted in an occluder, and a periapical radiograph was obtained using paralleling andbisecting technique with vertical angulation of -20, -15, -10, -5, 0, +5, +10, +15, and +20. The tooth length wasmeasured from the crown's highest point to the tooth apex's lowest end. Data obtained was then calculated usingSPSS. The result showed that the mean length of the lower premolar and molar was longer if the vertical angulationreached +20. Analysis with one-way ANOVA for the difference in the length of premolars, mesial root, and distalroot of lower molars between a direct measurement with digital caliper and measurement on periapical radiographstaken with paralleling technique and bisecting technique in all vertical angulations showed a p-value of 0,05.There were no significant differences in the mean length of lower premolars and the mesial and distal root of lowermolars between direct measurement using a digital caliper and measure on periapical radiographs taken withparalleling technique and bisecting technique in vertical angulations of -15, -10, -5, 0, +5, +10, +15, and +20.KEYWORDS: Vertical angulation, posterior tooth root morphology, periapical radiograph